1996
DOI: 10.1002/(sici)1099-081x(199611)17:8<645::aid-bdd986>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Primary Active Transport of Provastatin Across the Liver Canalicular Membrane in Normal and Mutant Eisai Hyperbilirubinaemic Rats

Abstract: We have previously demonstrated that the HMG‐CoA reductase inhibitor pravastatin is efficiently taken up by the liver via the ‘multispecific anion transporter’ in an active manner.3 To further examine the fate of pravastatin within the liver, its biliary excretion was studied in a single‐pass liver perfusion system and isolated liver canalicular membrane vesicles (CMVs) using normal (Sprague–Dawley rats; SDRs) and mutant Eisai hyperbilirubinaemic rats (EHBRs). In the liver perfusion experiments, the outflowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…However, Oat3-mediated transport does not account for the naringinsensitive pravastatin absorption observed in the present study because Oat3 is not expressed in rat intestine (35). Pravastatin is also reported to be a substrate of multidrug resistance-associated protein 2 (Mrp2) expressed in the bile canalicular membrane, based on comparative studies of biliary excretion of pravastatin in normal and Mrp2-dysfunctional Eisai hyperbilirubinemic rats (EHBR) (10,36). Therefore, Mrp2 is considered to be one of the transporters involved in the intestinal absorption process of pravastatin.…”
Section: Fig 2 Uptake Of Pravastatin Bymentioning
confidence: 99%
“…However, Oat3-mediated transport does not account for the naringinsensitive pravastatin absorption observed in the present study because Oat3 is not expressed in rat intestine (35). Pravastatin is also reported to be a substrate of multidrug resistance-associated protein 2 (Mrp2) expressed in the bile canalicular membrane, based on comparative studies of biliary excretion of pravastatin in normal and Mrp2-dysfunctional Eisai hyperbilirubinemic rats (EHBR) (10,36). Therefore, Mrp2 is considered to be one of the transporters involved in the intestinal absorption process of pravastatin.…”
Section: Fig 2 Uptake Of Pravastatin Bymentioning
confidence: 99%
“…The origins of this variation are not completely understood. The pharmacokinetics of pravastatin in rats are characterized by a low bioavailability, selective oatp-mediated uptake by the liver, substantial biliary excretion, and enterohepatic circulation (Komai et al, 1992;Yamazaki et al, 1996bYamazaki et al, ,c, 1997Hatanaka et al, 1998;Hsiang et al, 1999;Tokui et al, 1999). Only a small amount of pravastatin is excreted unchanged in the urine, and contribution of urinary excretion to total clearance is small (Komai et al, 1992;Hatanaka et al, 1998).…”
mentioning
confidence: 99%
“…However, dose-dependent nonlinear pharmacokinetics or saturable drug exposure is not observed in these mutant rats (Yamazaki et al, 1996;Kostrubsky et al, 2001). The findings indicate that substrates could be redirected from the canalicular to the sinusoidal membrane, then back into systemic circulation, and eventually secreted into urine.…”
Section: Discussionmentioning
confidence: 99%
“…The Mrp2-deficient animals, such as transport-deficient (TRϪ) and Eisai hyperbilirubinemic rats (EHBRs), have been used in the last decade as tools to study the importance of Mrp2/Abcc2-mediated hepatobiliary elimination (Sugawara et al, 1997). For instance, Yamazaki et al (1996) reported that the biliary secretion and total clearance of pravastatin were higher in normal rats, which resulted in 2-fold reduction in steady-state plasma concentration compared with Mrp2-deficient EHBRs. Similar work further confirmed the significant increase of systemic exposure and the decrease in biliary secretion of pravastatin (Kivistö et al, 2005) or troglitazone (Kostrubsky et al, 2001) in Mrp2-deficient TRϪ rats.…”
mentioning
confidence: 99%